BURNOUT IN BASIC EDUCATION TEACHERS AND WORKING CONDITIONS - Jacob, Marcelo (Health and Society, 2023)
This article addresses the phenomenon of Burnout among basic education teachers, exploring the main challenges they face and the causes related to working conditions. Burnout is a state of physical and emotional exhaustion resulting from chronic stress in the workplace, which negatively affects teachers’ well-being and the quality of education. The article analyzes the nature of Burnout, its manifestations, risk factors and consequences. In addition, prevention and intervention strategies are presented, such as institutional support, the development of coping skills and the promotion of balance between personal and professional life. Through a comprehensive review of the literature and consideration of case studies, this article offers an in-depth look at the topic of burnout in primary education teachers and highlights the importance of addressing this issue to improve the quality of education.